Renewable energy for sustainable mining - Alves, Wellington (2020)
Mining industry is known for requiring energy-intensive processes with significant impacts on the greenhouse gas emissions, which represents a major concern to both economic competitiveness of the sector and climate change. Low carbon sustainable technologies as renewable energy sources (RES) are emerging as key opportunities to sustainable mining in tandem with climate change challenges. However, the use of RES on this sector is still scarce even in countries well known for their mining potential and availability of renewable energy resources, as is the case of Brazil. This research investigates the economic viability of a proposed renewable-mining model for a mining company in the Northeast region of Brazil. The case of photovoltaic is analyzed considering the avoided electricity grid costs as potential benefits. The results showed that this renewable-mining strategy is promising for both PV and storage-PV.